Evidence of association of a BTA20 region peaked in ISL1 with puberty in Angus bulls - Fernandez, María Elena (2014)
In bovine, there are significant differences among and within breeds in the time when bulls reach puberty. Reported data indicate that age at puberty has a strong genetic component and is a multigenic trait. However, despite significant advancements in the field, the gene network controlling puberty is very complex, containing a host of genes that exert their effect on the hypothalamic–pituitary–gonadal (HPG) axis, and several aspects of regulation of the HPG axis are yet to be fully elucidated. The objective of this work was to identify new genes associated with age at puberty. Angus males (N=276) were weighted and scrotal circumference measured every month. When first bull calves reached 26 cm of scrotal circumference, sperm quality was added to the monthly measurements for the next three months. Based on sperm quality, two groups corresponding to the top and bottom 6.5% of the phenotypic distribution curve were selected to perform a genome-wide association study using a selective DNA approach, to be used as an exploratory analysis. Based on the results of this preliminary study, five SNPs located within BTA3, 20 and 24 associated regions were genotyped in the 276 bulls using pyrosequencing methods. This analysis allowed us to confirm the association of a BTA20 region with age at puberty estimated at C 50 million. The associated SNP explained 1.69% of the genetic variance of age at puberty at C 50 million. The associated region contained within and nearby positional candidate genes (ISL1, PELO, FST, SPZ1) that may be involved in spermatogenesis. Our results should encourage further investigation to confirm the role of these genes in order to increase our knowledge on genetic control of bovine puberty.